Agamben and Philosophical Archaeology - Hamidreza Mahboubi Arani; Abbas Jamali (Journal of Philosophical Investigations, 2022)
Methodology has a special place for every thinker, and this may be even more prominent in the humanities. This article seeks to examine the philosophical methodology of the contemporary Italian philosopher Giorgio Agamben. A methodology that, in his own words, owes much to Michel Foucault. The method is very important for Agamben. In fact, as we shall see, the method is not, in his view, a mere predetermined pattern, but, as is clear from the Greek word μέθοδος, method means "after the way," that is, after following the way. While Agamben has been talking about his methodology in some of his works shortly, in The Signature of All Things (2009), his main ideas could be seen. In this book, we encounter three main elements of Agamben's methodology: the paradigm, the signature, and the arche, all of which form a method that Agamben calls philosophical archeology. Agamben's methodology, or philosophical archaeology, is based on three basic elements with similar functions at different levels: paradigm, signature, and arche. In this article, these three concepts are examined, and in the last section, by examining their characteristics, it becomes clear how these three concepts form a method that Agamben calls philosophical archaeology.